Representation of cultural codes in Tuvan and Altai paremias about childhood - Kol, Choduraa Sh.; Nelyubova, Nataliya Yu.; Suvandii, Nadezhda D. (The New Research of Tuva, 2026)
The article analyzes cultural codes relating to children and childhood based on Tuvan and Altai paremias collected from authentic paremiographic sources. More than 40 representative Tuvan and Altai examples are presented. A comprehensive methodology is applied, according to which the ways of representing different cultural codes in paremias, their combinability, and their role in determining the significance of the theme of childhood in the linguistic and cultural consciousness of Tuvans and Altaians are specified.Elements denoting several cultural codes are identified, among which the animalistic code predominates in both languages. Its representatives demonstrate valency links with components naming the natural, vegetal, material, somatic, colour, numerical, and gastronomic codes.For the naming of children in Tuvan paremias, uses of both hyperonymic and hyponymic nominations are recorded. In the Altai material containing references to cultural codes, only hyperonymic designations of children are attested. Metaphorical designations of children in the two languages occur only fragmentarily. The representatives of the identified cultural codes appear predominantly in parallel syntactic constructions. They enhance the imagery and expressiveness of the paremias in conveying semantic proverbial condensates, which largely coincide in Tuvan and Altai proverbs about children and childhood.
Keywords: paremia; Tuvan language; Altai language; cultural code; childhood; child; animal young